A cross-sectional study to estimate the knowledge and practices regarding transfats among Panjab University students, Chandigarh - Singh, Kunal; Nandha, Ruchika; Prashar, Savita (International Journal Of Community Medicine And Public Health, 2022)
Background: Transfats also infamous as ugly fat is unsaturated fat which is formed in industries by hydrogenation of monosaturated fat by thermal processing etc. to make cheaper plant fat look like animal fat. Various organizations like FSSAI have given guidelines on transfats. WHO has committed to removing industrially produced transfats by 2023.Objectives of current study were to estimate the knowledge and practices about transfats among university students and do a comparative analysis of knowledge and practices about transfats among different groups of university students. Methods: The study was conducted at Panjab university. Total N=362. Data were analyzed and comparison was done on basis of gender, educational level, place of stay, and family income. Results: 72% students had knowledge regarding transfats, males (73%) had more knowledge than females (70%) (r=-0.09, p<0.05). Hostellers (85%) had more knowledge than day scholars (75%) and students staying in rented accommodation (60%) regarding transfats (r=-0.015, p<0.05), 58% students had good practices while remaining 42% lack good practices regarding transfats, students in rented accommodation (64%) had better practices than day scholars (32%) and hostellers (43%) regarding transfats (r=0.028, p<0.05). Conclusions: It was found youth lack awareness and knowledge (28%) regarding transfats, had wrong practices (42%) regarding transfats and the adoption of food containing transfats among youth is common.